Perancangan Kartu Pos Fotografis "Malang at Night" Sebagai Alternatif Cindera Mata Kota Malang - Tegar Andito; Sultan Arif Rahmadianto (ARTCHIVE: Indonesian Journal of Visual Arts and Design, 2021)
There are various souvenirs to be chosen that consist of keychains, traditional crafts, postcards, t-shirts, stickers, etc. Postcard is one of many kinds of souvenirs. Through postcard that being sent to friends or relatives, people can show ‘proof’ that they have visited certain places. Today that activity isn’t longer popular because of more modern means of communication. However, postcards are still desirable as inexpensive souvenirs to be collected by tourists themselves or to be given to friends and relatives without sending it through postal service. There aren’t many variations of Malang City postcards. This is caused by  postcards that labeled ‘Malang’ often show visual elements that exist in greater Malang area but not the Malang City itself. This effort to design postcard tries to  make an alternatives for souvenirs of Malang City in general and also specifically an alternative postcards of Malang City.